1996
DOI: 10.3354/meps139001
|View full text |Cite
|
Sign up to set email alerts
|

Foraging by murres (Uria spp.) at tidal fronts surrounding the Pribilof Islands, Alaska, USA

Abstract: We investigated the foraging distribution of 2 species of murres (Uria lomvia and U. aalge) in relation to Acoustically Determined Biomass (ADB) and hydrographic structure surrounding the Pribilof Islands, Bering Sea, Alaska, USA. The distribution and abundance of both murre species were similar; therefore, we combined data for thick-billed and common murres in the analysis. We found that murre densities were higher in frontal regions than in non-frontal regions. Maximum ADB was also found to be elevated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 16 publications
1
66
0
Order By: Relevance
“…This feature, which is evident along the entire southeastern shelf, limits the horizontal flux of salt, nutrients and heat between the middle and coastal domains (Coachman, 1986;Kachel et al, 2002). A similar feature occurs around the Pribilof Islands, where it enhances feeding opportunities for higher trophic level organisms (Kinder, Hunt, Schneider & Schumacher, 1983;Decker & Hunt, 1996;Hunt, Coyle, Hoffman, Decker & Flint, 1996a;Brodeur, Wilson & Ciannelli, 2000).…”
Section: The Eastern Bering Sea Regionmentioning
confidence: 93%
“…This feature, which is evident along the entire southeastern shelf, limits the horizontal flux of salt, nutrients and heat between the middle and coastal domains (Coachman, 1986;Kachel et al, 2002). A similar feature occurs around the Pribilof Islands, where it enhances feeding opportunities for higher trophic level organisms (Kinder, Hunt, Schneider & Schumacher, 1983;Decker & Hunt, 1996;Hunt, Coyle, Hoffman, Decker & Flint, 1996a;Brodeur, Wilson & Ciannelli, 2000).…”
Section: The Eastern Bering Sea Regionmentioning
confidence: 93%
“…The waters surrounding these islands are very productive in terms of prey concentrations due to structural fronts which exist around the 50 m isobath (Kinder et al 1983, Coyle & Cooney 1993, Brodeur et al 1997. However, these fronts are not likely to be a haven from predation since they are the feeding grounds for a large number of land-based piscivorous birds (mainly mur- Springer 1992, Decker & Hunt 1996. Since these birds and mammals are primarily visual predators, the time of greatest juvenile pollock vulnerability is likely to be during the day.…”
Section: 40mentioning
confidence: 99%
“…Perhaps food availability on the shelf in 2009 was sufficient to outweigh the additional energetic and time costs associated of commuting to the continental shelf-break/basin, and/or chick provisioning requirements confined day-time foraging trips. Certainly, previous studies have shown that Pribilof murres sometimes forage on the shelf in frontal areas associated with tidal currents and bottom topography (Decker and Hunt, 1996;Kokubun et al, 2008), with foraging efforts often focused below the thermocline in stratified water (Kokubun et al, 2008;Takahashi et al, 2008).…”
Section: Foraging Behaviormentioning
confidence: 99%